Fungsi dan Jenis Tindak Tutur pada Tajuk Rencana dalam Surat Kabar Kompas - Reni Aprianti; Edi Suryadi; F. A. Milawasri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2023)
This study aims to describe the functions and types of speech acts in the editorial in the March 2021 issue of Kompas. This research is a qualitative descriptive study. The subject of this research is editorial discourse in the March 2021 edition of the daily newspaper. The object of this research is the function of speech, and the types of speech that support speech acts in editorial discourse. The data obtained by listening method, reading and note-taking techniques. The data were analyzed using pragmatic and distribution analysis techniques. The main instrument of this research is the human instrument, which is self-research. The results of this study are the functions of speech acts found in the editorials of the March 2021 edition of the Kompas newspaper which consist of declarative, representative, expressive, directive, and commissive. The discourse in the editorial has the same characteristics as the news text. Both are used to convey criticism or opinions on policies, public services, and so on by using opinions or satirical sentences.